The E-Correspondence Principle - George W. Evans; Seppo Honkapohja (Center for Economic Studies and ifo Institute (CESifo), 2004)
We introduce the E-correspondence principle for stochastic dynamic expectations models as a tool for comparative dynamics analysis. The principle is applicable to equilibria that are stable under least squares and closely related learning rules. With this technique it is possible to study, without explicit solving for the equilibrium, how properties of the equilibrium are affected by changes in the structural parameters of the model. Even when qualitative comparative dynamics results are not obtainable, a quantitative version of the principle can be applied.
Keywords: 330; comparative dynamics; rational expectations; stability of equilibrium; adaptive learning; expectational stability